Indications of the SERPINE 1 variant rs1799768’s role in anti-VEGF therapy resistance in neovascular age-related macular degeneration - Muhammer Özgür ÇEVİK; Zühal Mert Altuntaş; Sadık Görkem Çevik (PLoS ONE, 2025)
Age-related macular degeneration (AMD) is a retinal disease prevalent in the elderly population, with two main subtypes: dry (non-exudative) and neovascular (wet or exudative). Neovascular AMD (nAMD) has a more debilitating prognosis than dry AMD, making it the third leading cause of blindness. Intravitreal injections of anti-vascular endothelial growth factor (IV anti-VEGF) are the most effective and widely accepted treatment for nAMD. However, a significant number of nAMD patients exhibit suboptimal responses to IV anti-VEGF therapy, with the underlying mechanisms not yet fully understood. We hypothesized that genetic polymorphisms associated with blood hypercoagulation may also contribute to suboptimal responses to IV anti-VEGF therapy. This study recruited 20 nAMD patients, who were divided into two groups based on their treatment responses after four years: 10 patients with suboptimal responses to IV anti-VEGF therapy and 10 patients with optimal responses. After obtaining institutional ethics board approval, we retrospectively evaluated relevant clinical records of twenty patients diagnosed with nAMD. Patient clinical data were accessed between 20th March 2021 -1st April 2021 for research purposes only. We genotyped peripheral blood DNA from each patient for hypercoagulation-related polymorphisms, including Factor V Leiden (rs6025), prothrombin c.20210G>A (rs1799963), MTHFR A1298C (rs1801131), MTHFR C677T (rs1801133), and SERPINE 1 (PAI-1-675 4G/5G) (rs1799768), and statistically compared the frequencies. Heterozygous and homozygous mutations in the SERPINE1 gene specifically PAI-1 promoter region PAI-1-675 4G/5G (rs1799768) were identified as risk factors for resistance to IV anti-VEGF therapy in nAMD patients (χ² test, p = 0.006). No other polymorphisms of the above-mentioned genes were statistically significant (p > 0.05). The failure of IV anti-VEGF therapy in nAMD patients may be influenced by various factors, one of which may be the inherited PAI-1-675 4G/5G (rs1799768) polymorphisms which normally known to contribute hypercoagulation. Further research involving a larger cohort is necessary to uncover the interplay between hereditary factors and other elements contributing to the inefficacy of IV anti-VEGF therapy in nAMD.